1998
DOI: 10.1590/s0100-879x1998000500001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gap junctions by protein phosphorylation

Abstract: Gap junctions are constituted by intercellular channels and provide a pathway for transfer of ions and small molecules between adjacent cells of most tissues. The degree of intercellular coupling mediated by gap junctions depends on the number of gap junction channels and their activity may be a function of the state of phosphorylation of connexins, the structural subunit of gap junction channels. Protein phosphorylation has been proposed to control intercellular gap junctional communication at several steps f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 66 publications
2
50
0
2
Order By: Relevance
“…An indirect effect of S. aureus on astrocyte Cx26 expression could be envisioned to occur through an autocrine/paracrine action since both TNF-α and IL-1β are capable of activating MAPK pathways upon binding to their cognate receptors (Hanada and Yoshimura, 2002). Since Cx26 is not phosphorylated it is more likely that any indirect effects of proinflammatory stimuli would be exerted at the level of transcription/ translation (Kojima et al, 1999;Saez et al, 1998Saez et al, , 2005Traub et al, 1989). Although Temme et al (1998) have reported that IL-1 and TNF-α augment Cx26 while decreasing Cx32 mRNA expression in hepatocytes, to our knowledge, the role of proinflammatory mediators on modulating Cx26 levels in astrocytes has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…An indirect effect of S. aureus on astrocyte Cx26 expression could be envisioned to occur through an autocrine/paracrine action since both TNF-α and IL-1β are capable of activating MAPK pathways upon binding to their cognate receptors (Hanada and Yoshimura, 2002). Since Cx26 is not phosphorylated it is more likely that any indirect effects of proinflammatory stimuli would be exerted at the level of transcription/ translation (Kojima et al, 1999;Saez et al, 1998Saez et al, , 2005Traub et al, 1989). Although Temme et al (1998) have reported that IL-1 and TNF-α augment Cx26 while decreasing Cx32 mRNA expression in hepatocytes, to our knowledge, the role of proinflammatory mediators on modulating Cx26 levels in astrocytes has not yet been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the connexins not only contain protein kinase "consensus phosphorylation sequences", but have also been demonstrated to be phosphorylated by kinases in vitro and in some cases in cell culture or tissues. In addition, many connexins (Cx31, Cx32, Cx37, Cx40, Cx43, Cx45, Cx46, Cx50 and Cx56) have been shown to be phosphoproteins by either a shift in their electrophoretic mobility or direct incorporation of 32 P Saez et al, 1998), and we expect this list to grow as recently discovered family members are investigated. Functional data related to phosphorylation has been reported for Cx32, Cx43, Cx45 and Cx56.…”
Section: General Aspects Of Connexin Phosphorylationmentioning
confidence: 99%
“…Connexin phosphorylation has been previously reviewed Saez, Martinez, Branes, & Gonzalez, 1998;Stagg & Fletcher, 1990) and, thus, this review concentrates on the most recent developments. The total number of references has been limited by the journal and, thus, we apologize in advance for the curtailed citations and the use of reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, regulation of these channels by hormones and other extracellular signaling molecules such as neurotransmitters, growth factors and cytokines has been demonstrated at the level of transcription, mRNA stability, translation, cytoplasmic traffic and gating (1,6,7). So far, the best studied mechanism operating during these regulatory processes is the phosphorylation/dephosphorylation (6) of connexins, transcription factors and other regulatory proteins.…”
Section: General Aspects Of Gap Junction Modulation By Extracellular mentioning
confidence: 99%
“…For instance, connexin 43 allows the passage of lucifer yellow while Cx45 does not (3). In addition, the functionality of heterologous gap junctions has been shown to depend on selective compatibility among different connexins (3,4 Gap junction channels can be gated, i.e., "opened" or "closed", by several agents including Ca 2+ , H + , lipophilic substances, voltage gradients, and hormones (1), the latter generally acting via activation of protein kinases that phosphorylate the cytoplasmic regions of several connexins (6,7), or in some cases by phosphatases (6,7). The presence of connexins has been demonstrated in distinct lympho-hematopoietic organs where their function is not clear (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%